Reconstruction of Legal Protection Policy for Justice Collaborators in Corruption Crimes - Suyanto R. Sumarta; Azis Budianto (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This research aims to explore and reconstruct the legal protection policy for justice collaborators in corruption crimes in Indonesia. Although their existence is vital in combating corruption, many perpetrators are reluctant to come forward due to uncertainty in protection and the potential risks they face. Weaknesses in the existing policies, including a lack of transparency and adequate security guarantees, hinder perpetrators from collaborating with law enforcement. Therefore, this research identifies various challenges faced by justice collaborators and highlights the importance of comprehensive legal protection reform. This study offers recommendations for appropriate and effective legal protection efforts for justice collaborators in handling corruption cases. By analyzing protection practices in other countries and applying restorative justice principles, this research aims to provide solutions that not only protect justice collaborators but also enhance public trust in the justice system. It is hoped that the results of this research can contribute to formulating more effective and responsive policies to meet the protection needs of justice collaborators in Indonesia, encouraging more perpetrators to bravely come forward in the fight against corruption.